Extended Abstracts of the 2019 CHI Conference on Human Factors in Computing Systems 2019
DOI: 10.1145/3290607.3299055
|View full text |Cite
|
Sign up to set email alerts
|

Lessons Learned from Research via Private Social Media Groups

Abstract: As research methods evolve to provide a voice to understudied, distributed communities, we explore our experiences running and analyzing Asynchronous Remote Communities (ARC) studies. Our experiences stem from four separate Facebook-based ARC studies with people who experience: rare disease, pregnancy, miscarriage, or HIV. We delve into these studies' methods, and present updated guidelines focused on improved study design, data collection, and analysis plans for ARC studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…A further strength of this method was that, although potentially novel in its use, it remained evidence-based in the asynchronous remote community (ARC) literature. Previous research has suggested optimal methods of recruitment (online networks); content (a friendly and informal atmosphere, posting often, similar prompts to in-person focus groups); sample size (between 13 and 48 participants); facilitator role (to respond quickly to questions, post prompts at similar times daily) and analysis method (content analysis), which this study followed closely (5,10,12,13,25). Additionally, given that this method allowed for participants to take as much time as needed to consider and respond to a prompt -in contrast to the immediacy of in-person interviews and focus groups -another strength could be increased thoughtfulness of answers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A further strength of this method was that, although potentially novel in its use, it remained evidence-based in the asynchronous remote community (ARC) literature. Previous research has suggested optimal methods of recruitment (online networks); content (a friendly and informal atmosphere, posting often, similar prompts to in-person focus groups); sample size (between 13 and 48 participants); facilitator role (to respond quickly to questions, post prompts at similar times daily) and analysis method (content analysis), which this study followed closely (5,10,12,13,25). Additionally, given that this method allowed for participants to take as much time as needed to consider and respond to a prompt -in contrast to the immediacy of in-person interviews and focus groups -another strength could be increased thoughtfulness of answers.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have conducted focus-group style research in private or secret Facebook groups (5), with the purpose of conducting a needs analysis or collecting data in a more focus-group style to understand a problem. Research groups at the University of Indiana and the University of Edinburgh have particular experience with Asynchronous Remote Communities, or focus groups occurring online in which participants are not online at the same time, and have published widely on the topic -primarily short reports with recommendations for future research and lessons learned (12,13). However, none of the studies we have found to date use asynchronous remote communities, particularly in a secret Facebook group, to co-design an intervention for future testing.…”
Section: The Internet As a Tool For Co-productionmentioning
confidence: 99%
“…A further strength of this method was that, although potentially novel in its use, it remained evidencebased in the asynchronous remote community (ARC) literature. Previous research has suggested optimal methods of recruitment (online networks); content (a friendly and informal atmosphere, posting often, similar prompts to in-person focus groups); sample size (between 13 and 48 participants); facilitator role (to respond quickly to questions, post prompts at similar times daily) and analysis method (content analysis), which this study followed closely (5,10,12,13,25). Additionally, given that this method allowed for participants to take as much time as needed to consider and respond to a prompt -in contrast to the immediacy of in-person interviews and focus groups -another strength could be increased thoughtfulness of answers.…”
Section: Discussionmentioning
confidence: 99%
“…A further strength of this method was that, although potentially novel in its use, it remained evidencebased in the asynchronous remote community (ARC) literature. Previous research has suggested optimal methods of recruitment, content, sample size and analysis method, which this study followed closely (5,9,10). Additionally, given that this method allowed for participants to take as much time as needed to consider and respond to a prompt -in contrast to the immediacy of in-person interviews and focus groups -another strength could be increased thoughtfulness of answers.…”
Section: Discussionmentioning
confidence: 99%